IgA+ memory B-cells are significantly increased in patients with asthma and small airway dysfunction. Issue 5 (3rd November 2022) - Habener, Anika; Grychtol, Ruth; Gaedcke, Svenja; DeLuca, David; Dittrich, Anna-Maria; Happle, Christine; Abdo, Mustafa; Watz, Henrik; Pedersen, Frauke; König, Inke Regina; Thiele, Dominik; Kopp, Matthias Volkmar; et al.
Background: Comprehensive studies investigated the role of T-cells in asthma which led to personalised treatment options targeting severe eosinophilic asthma. However, little is known about the contribution of B-cells to this chronic inflammatory disease. In this study we investigated the contribution of various B-cell populations to specific clinical features in asthma. Methods: In the All Age Asthma Cohort (ALLIANCE), a subgroup of 154 adult asthma patients and 28 healthy controls were included for B-cell characterisation by flow cytometry. Questionnaires, lung function measurements, blood differential counts and allergy testing of participants were analysed together with comprehensive data on B-cells using association studies and multivariate linear models. Results: Patients with severe asthma showed decreased immature B-cell populations while memory B-cells were significantly increased compared with both mild–moderate asthma patients and healthy controls. Furthermore, increased frequencies of IgA + memory B-cells were associated with impaired lung function and specifically with parameters indicative for augmented resistance in the peripheral airways. Accordingly, asthma patients with small airway dysfunction (SAD) defined by impulse oscillometry showed increased frequencies of IgA + memory B-cells, particularly in patients with mild–moderate asthma. Additionally, IgA + memory B-cells significantly correlated with clinical features of SAD such as exacerbations. Conclusions: With this study we demonstrate for the first time a significant association of increased IgA + memory B-cells with asthma and SAD, pointing towards future options for B-cell-directed strategies in preventing and treating asthma. Circulating B-cells are altered in asthma patients. In particular, IgA + memory B-cells are significantly increased in patients with impaired lung function, especially of the small airways, suggesting a contribution to inflammation in the peripheral lung. https://bit.ly/3r0xBNA